Penerapan Model Pembelajaran Flipped Classroom dalam Pelajaran Geografi untuk Meningkatkan Keaktifan Siswa di SMAN 1 Batipuh - Syafitri, Gita Isma; Rianto, Slamet; Yuherman, Yuherman (LaGeografia, 2023)
The background of this research is the active learning caused by the lack of students asking questions and the absence of participation in helping friends during discussions. The type of research used is quasi-experimental research. The research design used was the Pretest-Posttest Control Group Design X SMAN 1 Batipuh which was registered for the 2022 – 2023 academic year consisting of 9 classes with a total of 306 students. The sampling in this study was random sampling. The results of the study: 1) The activeness of the students in the Geography experimental class in class X.E 3 at Sman 1 Batipuh Academic Year 2022/2023, obtained an average percentage value of 80.54% which was classified as "Very good while the Geography Control class, obtained an average The average percentage is 58.07% which is classified as "Pretty Good. Test Requirements Analysis For p values less than 0.05 (p = 0.000 <0.05), the results of the t-test show that there is a significant difference between using Flipped Classroom and Conventional Learning and see the difference in the average value of the Posttest using the conventional learning model has an average value of 57.51, while after using the treatment the learning model has increased to 83.77. So, the difference is an increase of 26.26 from using the conventional learning model to the Flipped Classroom. AbstrakPenelitian ini dilatar belakangi pada keaktifan belajar yang disebabkan karena kurangnya siswa dalam bertanya, tidak adanya partisipasi dalam membantu teman saat berdiskusi.. Jenis penelitian yang digunakan adalah penelitian quasi exsperimen. Desain penelitian yang digunakan adalah Pretest-Posttest Control Group Design X SMAN 1 Batipuh yang terdaftar pada tahun ajaran 2022 – 2023 terdiri atas 9 kelas dengan jumlah 306 siswa. Pengambilan sampel pada penelitian ini secara random sampling. Hasil penelitian :1) Keaktifan siswa kelas ekperimen mata pelajran Geografi pada kelas X.E 3 di Sman 1 Batipuh Tahun Ajaran 2022/2023, memperoleh nilai persentase rata – rata sebesar 80,54% yang tergolong kedalam “Sangat baik sementara kelas  Kontrol geografi, memperoleh nilai persentase rata-rata sebesar 58,07% yang tergolong kedalam “Cukup baik. UJi Persyaratan analisis Untuk nilia p lebih kecil dari 0,05 (p=0,000<0,05) jadi, demikian hasil uji-t tersebut menunjukkan terdapat perbedaan yang signifikan menggunakan Pembelajaran Flipped Classroom dan Konvensional  dan di lihat Perbeadaan nilai rata-rata Postest menggunakan model pembelajaran Konvensional nilai rata-rata nya 57,51 sedangkan setaleh menggunakan perlakuan model pembelajaran mengalami peningkatan menjadi 83,77. jadi, selisihnya peningkatanya sebesar 26,26 dari menggunakan model pembelajaran Konvensional ke Flipped Clasroom.